Harm Reduction and War on Drugs in Indonesia During Joko Widodo Era - Yeyen Subandi; Ananda Dewin Ikhtiarin; Harits Dwi Wiratma; Maria Veri Diana Baun Yue; Tanti Nurgiyanti; Ariel Nethan; Diansari Solihah Amini; Viola Marsela Agustin; Bagus Subekti Nuswantoro (PT FORMOSA CENDEKIA GLOBAL, 2022)
Narcotics is a form of transnational crime. From the practice of narcotics crime, many victims of the nation's generation. Circulation and abuse of narcotics are some of the problems facing the world, including Indonesia. Estimated data on narcotics users in Indonesia is between 3.7-4 million people (National Narcotics Agency). Various efforts have been made by the Indonesian government to break the chain of narcotics trafficking and abuse through international collaboration with the Harm Reduction (HR) program. The era of President Joko Widodo (Jokowi) of the Indonesian government was more towards the